A REVIEW OF MATHEMATICAL MODELING OF CARBON POLLUTION BY VEHICLES ON HIGHWAYS WITH HUGE EMBANKMENTS - Awino, John Otieno; Onyango, Thomas; Okelo, N. B. (IJRDO -JOURNAL OF MATHEMATICS, 2015)
In this paper, we review developed mathematical models for carbon pollution and investigate the level of carbon pollutants on the highways and how it spreads to the people held up in traffic jams and those residing closer to the highways in Kenya.